A humanized bone microenvironment uncovers HIF2 alpha as a latent marker for osteosarcoma. (15th April 2019) - Wagner, Ferdinand; Holzapfel, Boris M.; Martine, Laure C.; McGovern, Jacqui; Lahr, Christoph A.; Boxberg, Melanie; Prodinger, Peter M.; Grässel, Susanne; Loessner, Daniela; Hutmacher, Dietmar W.
Graphical abstract: Abstract: The quest for predictive tumor markers for osteosarcoma (OS) has not well progressed over the last two decades due to a lack of preclinical models. The aim of this study was to investigate if microenvironmental modifications in an original humanized in vivo model alter the expression of OS tumor markers. Human bone micro-chips and bone marrow, harvested during hip arthroplasty, were implanted at the flanks of NOD/scid mice. We administered recombinant human bone morphogenetic protein 7 (rhBMP-7) in human bone micro-chips/bone marrow group I in order to modulate bone matrix and bone marrow humanization. Ten weeks post-implantation, human Luc-SAOS-2 OS cells were injected into the humanized tissue-engineered bone organs (hTEBOs). Tumors were harvested 5 weeks post-implantation to determine the expression of the previously described OS markers ezrin, periostin, VEGF, HIF1α and HIF2α. Representation of these proteins was analyzed in two different OS patient cohorts. Ezrin was downregulated in OS in hTEBOs with rhBMP-7, whereas HIF2α was significantly upregulated in comparison to hTEBOs without rhBMP-7. The expression of periostin, VEGF and HIF1α did not differ significantly between both groups. HIF2α was consistently present in OS patients and dependent on tumor site and clinical stage. OS patients post-chemotherapy had suppressed levels of HIF2α. In conclusion, we demonstrated the overall expression of OS-related factors in a preclinical model, which is based on a humanized bone organ. Our preclinical research results and analysis of two comprehensive patient cohorts imply that HIF2α is a potential prognostic marker and/or therapeutic target. Statement of Significance: This study demonstrates the clinical relevance of the humanized organ bone microenvironment in osteosarcoma research and validates the expression of tumor markers, especially HIF2α. The convergence of clinically proven bone engineering concepts for the development of humanized mice models is a new starting point for investigations of OS-related marker expression. The validation and first data set in such a model let one conclude that further clinical studies on the role of HIF2α as a prognostic marker and its potential as therapeutic target is a condition sine qua non.